Applying agent technology to facilitate knowledge sharing among bioinformatics communities of practice - Abdullah, Rusli; Ibrahim, Hamidah; Atan, Rodziah; Napis, Suhaimi; Jaafar, Azmi; Selamat, Mohd Hasan; Hairudin, Nurul Haslina; Hamidon, Siti Hernazura (2008)
Agent technology is a software programs or tool that could be developed and used to facilitate and support the community of practice (CoP) especially the bioinformatics communities who are involved in managing bioinformatics activities such as collective and organized, and shared knowledge in term of best practice and lesson learnt in order to perform their worked for better solutions and competativeness. This paper describes on the theoretical concept and approach of agent technology framework that could be developed in implementing bioinfomatics knowledge management system (BKMS) in order to facilitate knowledge sharing among bioinformatics communities as well as to demonstrates it into the system wise; on how the agent technology could be utilized in the BKMS as a system model for serving the communities that is developed by using groupware such as Lotus Notes software. The achievement in conducting this framework of the BKMS is an added value for the any organization that need to implement the BKMS as a system, which could be helped the CoPs to work together in achieving their aims and mission statements. The emphasis also will be given to the BKMS activities that may concern for agent technology to help the CoPs especially in working collaboratively including critical success factor (CSF) in order to ensure that BKMS initiatives would be delivered competitive advantage for the CoP as well as thier organization.